Control of the Boar in the Mantiqueira Range: a Case Study in the Itatiaia National Park and RPPN Alto Montana - Alves da Rosa, Clarissa (2018)
The wild pig (Sus scrofa) is an invasive alien species that has been causing social and environmental impacts worldwide. Nowadays, wild pigs occupy almost all Brazilian regions, with high densities in the tropical forests of the Atlantic Forest. Wild pigs control is authorized in Brazil since 2013, and can be carried out by any Brazilian citizen authorized by environmental agencies. In this paper, we present the case study of an experimental control of wild pigs carried out at the Private Reserve of Natural Heritage Alto Montana and Itatiaia National Park, in the Serra da Mantiqueira, a key area for conservation of the Atlantic Forest and biodiversity of the world. Our work was carried out between 2013 and 2015, where we planned and executed a pilot plan for wild pigs control in collaboration with local community, technicians, managers and researchers. Wild pigs control actions were carried out in partnership with volunteer controllers from local community and with the management of Protected Areas (PAs). The collaboration between local community, researchers and managers was very positive for wild pigs control in Serra da Mantiqueira. However, the absence of official guidelines for wild pigs control within federal PAs leaves managers and servers vulnerable and insecure about performing capture and killing activities of a feral species within a protected area. Finally, from the experience gained in this work, we recommend some actions that may help the ICMBio (environmental agency responsible for the management of federal PAs) in the elaboration of rules and guidelines for wild pigs control within PAs and including the local community.